3 - Responding to Poverty in the Light of the Post-Development Debate: Some insights from the NGO Enda Graf Sahel: by Sally Matthews - Matthews, Sally (Africa Development, 2006)
How can we take on board the many valuable insights of post-development theory without seeming to advocate indifference and inaction in the face of the misery that many people in the world experience daily? In this paper, I provide a partial response to this question. I begin by looking at some of the alternative strategies offered in post-development literature and set out to show that while there are several problems with these alternatives, to read post-development theory as advocating indifference or inaction is to read it uncharitably. Sec- ondly, I draw on the experiences of the non-governmental organisation (NGO) Enda Graf Sahel in Dakar, Senegal to suggest some ways in which the insights of post-development theory, or some versions of post-development theory, can be taken into consideration without leading to inaction or indifference in the face of the suffering of those who occupy a less advantaged position in contemporary relations of power and privilege.